2013
DOI: 10.1007/s10900-013-9769-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Childhood Asthma Symptoms: An Ecological Study in Urban Latin America

Abstract: Asthma is an important public health problem in urban Latin America. This study aimed to analyze the role of socioeconomic and environmental factors as potential determinants of asthma symptoms prevalence in children from Latin American (LA) urban centers. We selected 31 LA urban centers with complete data, and an ecological analysis was performed. According to our theoretical framework, the explanatory variables were classified in three levels: distal, intermediate, and proximate. The association between vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Hispanic America faces unique challenges, as a high proportion of its population is now urban in the context of high rates of poverty, a polluted environment, and limited access to sanitation (4, 52). Consistent with worldwide literature (53), low socioeconomic status (SES) in/near urban areas, high levels of inequality, and urbanization are associated with childhood asthma in Hispanic America (54)(55)(56)(57).…”
Section: Socioeconomic Status and Urbanizationsupporting
confidence: 60%
“…Hispanic America faces unique challenges, as a high proportion of its population is now urban in the context of high rates of poverty, a polluted environment, and limited access to sanitation (4, 52). Consistent with worldwide literature (53), low socioeconomic status (SES) in/near urban areas, high levels of inequality, and urbanization are associated with childhood asthma in Hispanic America (54)(55)(56)(57).…”
Section: Socioeconomic Status and Urbanizationsupporting
confidence: 60%
“…A similar study was done with data from the Latin American International Study of Asthma and Allergies in Childhood to analyze multiple factors relating to asthma prevalence (Fattore, Santos, & Barreto, 2014). This study also found that the Gini index, which is a measure of income distribution similar to SES, along with crowding, sanitation, infant mortality rate, and homicide rate, explains 75% of the variability in asthma prevalence between 31 Latin American urban centers (Fattore et al, 2014). This study, along with the two discussed earlier, utilized a cross-sectional design that prevents any causational inferences to be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…Fattore, Santos, and Barreto (2014) measured socioeconomic and environmental determinants of wheezing in children in Latin America as described above. Similarly, Holt, Theall, and Rabito (2013) and Keet et al (2015) analyzed data on the sociodemographic, neighborhood, familial, and individual level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cooking in the same room where the family lives may increase the exposure to particulate matters (PM 2.5 ) which can exacerbate asthma (14). Other triggers include use of detergent such as bleach (sodium hypochlorite), which is widely used in Syria (15) and amongst the shelter dwellers, exposure to SHS (16,17) and poverty (17,18) (the study participants had an average daily income of less than 2 USD/day). Finally, our spirometry data also suggested that both asthma and COPD were severely under-diagnosed, and thus not adequately managed.…”
Section: Discussionmentioning
confidence: 99%